Analisis Sistem Informasi Akuntansi Penjualan Dan Penerimaan Kas Produk Gadai Kca Pada PT. Pegadaian Upc. Cibadak - Suprianti, Miranti; Martaseli, Evi; Eriswanto, Elan (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to explain the application of sales accounting information system and accounting information system for cash receipts of KCA pawn products at PT. Pawnshops and identify the obstacles faced in the use of the accounting information system used. The object of research in this study is the sales Accounting Information System (SIA) and the Cash Receipt Accounting Information System for KCA pawn products. The data used is descriptive from primary and secondary data sources. The research method used is a qualitative research method with a descriptive approach with interview, observation, and documentation data collection methods. The results of the data that have been obtained are then analyzed using data analysis techniques before in the field and data analysis during and after in the field, namely data reduction, data presentation, and conclusions. The results of this study show that the sales and cash receipt accounting information system used by PT. Pegadaian (Persero) UPC Cibadak has been implemented well and in accordance with the company's SOP. Then the identified obstacles also have their own solutions.